ð˜ˆð˜¯ð˜µð˜©ð˜°ð˜¯ð˜°ð˜®ð˜¶ð˜´ ð˜¨ð˜³ð˜¢ð˜¯ð˜¥ð˜ªð˜´ Boheman (Curculionidae) JÃ ESTÃ NA LAVOURA ALGODOEIRA DO BRASIL - Habib, M. E. M.; Fernandes, W. D. (REVISTA DE AGRICULTURA, 2020)
ð˜ˆð˜¯ð˜µð˜©ð˜°ð˜¯ð˜°ð˜®ð˜¶ð˜´ ð˜¨ð˜³ð˜¢ð˜¯ð˜¥ð˜ªð˜´ Boheman (Curculionidae) JÃ ESTÃ NA LAVOURA ALGODOEIRA DO BRASIL